Analisis Putusan Hakim No. 180/Pid.Sus/2020/PN Sda terhadap Korban Tindak Pidana Kekerasan dalam Rumah Tangga - Fauzi, Lutfiah; Rosnawati, Emy (ResearchJet Journal of Analysis and Inventions, 2024)
Victims of domestic violence are mostly experienced by women and must get protection from society and the state in order to avoid and be free from violence and torture that has degraded the degree and dignity of human beings. Domestic violence, especially the atrocities committed by partners against their partners, leads not only to real torture but also to mental misery. Therefore, victims of domestic violence must receive maximum protection. The purpose of this study is to find out the analysis of the judge's decision No.180/Pid.Sus/2020/PN Sda. This type of research is a normative juridical research using a case approach problem approach. Sources of legal materials obtained in this study are primary and secondary sources of law. While the analysis of legal materials used in this study is deductive analysis because deductive analysis is a technique of analyzing legal materials by collecting facts that are packaged into theories. The results of the analysis of the judge's decision No.180/Pid.Sus/2020 PN. SDA against victims of criminal acts of domestic violence shows that the judge in imposing criminal sanctions on the defendant has been in accordance with the applicable law, namely Article 44 paragraph 1 of the Law on the Elimination of Domestic Violence. However, there was injustice. The judge tried the decision no. 180/Pid.Sus/2020 PN. Sda because what was handed down to the defendant was 3 years in prison. In the judge's decision there is injustice because in Article 44 paragraph (1) of the Law. RI. Number 23 of 2004 concerning the Elimination of Domestic Violence has regulated that criminal acts of domestic violence must be sentenced to a maximum of 5 (five) years in prison and a fine of Rp. 15,000,000.